Evaluation of heavy-ion impact in bulk and FDSOI devices under ZTC condition. (September 2017) - Calienes, W.E.; de Aguiar, Y.Q.; Meinhardt, C.; Vladimirescu, A.; Reis, R.
Abstract: This work examines the effects of heavy-ion impact under temperature variation. A NMOS device in 32 nm bulk and 28 nm FDSOI were analysed through TCAD simulations. In order to overcome the temperature effects, both devices were conducted to the Zero Temperature Coefficient (ZTC) condition. The results demonstrate a reduction from 5% up to 18% on the total collected charge and lower variation due to temperature fluctuation when the devices are operating in ZTC condition. Highlights: The effect of heavy ion impact in ZTC condition is analysed for 32nm Bulk CMOS and 28nm FDSOI devices. Devices operating in ZTC condition presents reduction on the total CC and less variation due to temperature fluctuation. In both devices, the Low doping Drain (LDD) is the most sensitive region against the heavy ion impact effects. The FDSOI device shows a reduction up to 18% in the total CC, while the Bulk device can reach up to 8% of reduction.